Creation of Dhemit Theater Works as a Character Education Media for Generation Z at the Palangka Raya Mapas Studio: Penciptaan Karya Teater Dhemit sebagai Media Pendidikan Karakter untuk Generasi Z Di Sanggar Mapas Palangka Raya - Mayangsari, Marrisa Aulia Mayangsari; Afrom, Ichyatul; Girindraswari, Nawung Asmoro; Pratiwi, Endah Yusma (Universitas Negeri Surabaya, 2024)
Abstract: This study examines efforts to instill character education for Generation Z at the Mapas Studio, Palangka Raya, through creating Dhemit theater works. Generation Z are people born between the 2000s and 2010s. The challenge currently facing the world of education is implementing the right strategy to provide academic knowledge while forming strong characters and positive personality qualities for Generation Z. The research method used a qualitative approach to creating works of art, namely searching for ideas, designing works, and realizing works. Data was obtained through field notes, observations, and literature studies. The results of this study found that aspects of the Character Education Strengthening program from the Ministry of Education and Culture, namely teaching the values ​​of Integrity, Religiousness, Nationalism, Independence, and Mutual Cooperation, were all obtained by members of the Mapas Studio through the process of creating Dhemit theater works. Keywords: Creation of Theater Works , Character Education for Generation Z.